2015
DOI: 10.1016/j.canlet.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel system for the culture and expansion of hepatic stem-like cancer cells

Abstract: Hepatocellular carcinoma (HCC) is a major primary liver malignancy in adults. Despite the progress made, the outcome of the treatment to this disease is less than satisfactory as the post therapy tumor recurrence is almost inevitable. Accumulating pieces of evidence have suggested that the recurrence is due to the existence of a subpopulation of the HCC cells that possess the properties of stem cells and are resistant to radiation and chemotherapy. It is therefore important to understand the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Moreover, EGF that we add to TSM was essential to support proliferation of CSCs, such as colon cancer stem cells (Feng et al, 2012), neuroblastoma initiating cell (Hansford et al,2007) and hepatic stem-like cells (Li, et al, 2015). In our study, MHCC97H cells were cultured in the presence of 10% FBS as monolayers of adherent cells ( Figure 1AI) and subsequently in TSM.…”
Section: The Parental Mhcc97h Cells Could Form Self-renewing Spheresmentioning
confidence: 81%
“…Moreover, EGF that we add to TSM was essential to support proliferation of CSCs, such as colon cancer stem cells (Feng et al, 2012), neuroblastoma initiating cell (Hansford et al,2007) and hepatic stem-like cells (Li, et al, 2015). In our study, MHCC97H cells were cultured in the presence of 10% FBS as monolayers of adherent cells ( Figure 1AI) and subsequently in TSM.…”
Section: The Parental Mhcc97h Cells Could Form Self-renewing Spheresmentioning
confidence: 81%
“…Similarly, Li et al enriched CSCs from human HCC cell lines and human primary HCC tumors by the sphere-forming assay. These cells exhibited high expression of CD90 and mesenchymal marker Vimentin [71]. …”
Section: Emt Phenotypic Cells As a Resource For Hepatic Cscsmentioning
confidence: 99%
“…Subsequently, combination gene therapy was carried out to observe the prevention and recurrence of tumor metastasis. Gene therapy comprises the transfer of one or more genes of interest, as well as their products, safely and effectively into target cells in vivo (Li et al, 2015b). In the present study, we applied OIIT, and the results showed that the luciferase gene could be inserted into DNA molecules to observe the results of gene therapy.…”
Section: Discussionmentioning
confidence: 77%